INTERVENCIÓN PSICOSOCIAL EN RADICALIZACIÓN TEMPRANA: ABORDAJE CON METODOLOGÍA SCRUM. - RODRÍGUEZ-RODRÍGUEZ, JUAN CARLOS; RODRÍGUEZ-GÓNGORA, JOSEFINA (Human Review, 2022)
The main objective of this manuscript is to present a new methodology for addressing violent radicalization using the Scrum methodology, widely used in software construction environments, as the main tool. A work methodology focused on the recipients of the intervention is proposed. The Scrum method has been shown, on many occasions, to be very effective as a collaborative learning strategy, having been used in university environments for the development of high-quality projects for short periods of time. Addressing the charter of values and intervening towards values incompatible with violence will reduce radicalization in adolescents.